THE PRE-PRESIDENTIAL ELECTION 2024: UNCOVERING THE CONSISTENCY OF RELIGIOUS POLITICIZATION - Achfandhy, Mochammad Irfan; Pujianto, Wawan Trans; Daniyarti, Wiwi Dwi; Jamiah, Ririn (Universitas Islam Negeri Ar-Raniry, 2024)
Social media is an effective communication tool for facilitating political campaign activities. However, social media promotes the enormous politicization of religion, such as the controversy surrounding the mixing of politics and religion in Indonesia's 2017 and 2019 general elections. This study aims at responding to the causes of social media supporting the consistency of the politicization of religion in the Pre-Presidential General Election 2024 by employing the politicization of religion in the past as a reflection of the current phenomenon. The research was conducted using a qualitative strategy and multimodal discourse analysis as an instrument for data analysis. Data was collected from the Twitter account @aniesbaswedan from October to December 2022 and previous studies. The research results indicate that the nuances can demonstrate indicators of the consistency of the politicization of religion through multimodal content, such as text, images, video, audio, and animation. The multimodal aspect can frame politics with an intriguing blend of religious attributes to obtain responses from netizens. Media convergence also stimulates interactive communication between netizens with others. In conclusion, politicians implement religious symbols to increase netizens' response in its campaign.